Career progression and formal versus on-the-job training - Jerome Adda; Christian Dustmann; Costas Meghir; Jean-Marc Robin (Institute for Fiscal Studies (IFS), 2009)
We model the choice of individuals to follow or not apprenticeship training and their subsequent career. We use German administrative data, which records education, labour market transitions and wages to estimate a dynamic discrete choice model of training choice, employment and wage growth. The model allows for returns to experience and tenure, match specific effects, job mobility and search frictions. We show how apprenticeship training affects labour market careers and we quantify its benefits, relative to the overall costs. We then use our model to show how two welfare reforms change life-cycle decisions and human capital accumulation: One is the introduction of an Earned Income Tax Credit in Germany, and the other is a reform to Unemployment Insurance. In both reforms we find very significant impacts of the policy on training choices and on the value of realized matches, demonstrating the importance of considering such longer term implications.
Keywords: 330; Arbeitsmarkt; Arbeitsmobilität; Betriebliche Ausbildung; Berufsbegleitende Ausbildung; Arbeitslosenversicherung; Einkommensteuerrecht; Wirtschaftsmodell